2014
DOI: 10.1039/c4tc01362j
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion complexes of fullerenes with flexible tetrathiafulvalene derivatives bearing four aryls through sulfur bridges

Abstract: TTF derivatives decorated with four aryls through the sulfur bridges are employed to form the donoracceptor type inclusion complexes with fullerenes. The key factor for the formation of inclusion complexes is the introduction of structural flexibility in TTF molecules along with the molecular size matching with fullerenes. A crystallographic study indicates that the structures of the resulting complexes are stabilized by a multidimensional intermolecular interaction network consisting of TTF cores, peripheral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…On the basis of hundreds of experimental runs, we found that the Ar-S-TTFs possessing the first redox potential ( E 1/2 1 ) smaller than 0.6 V could form the co-crystal-type complexes with fullerene molecules C 60 and/or C 70 , whereas those with E 1/2 1 > 0.6 V could not afford the desired complexes. The complexes obtained thus far are intrinsically neutral [ 63 ], which means the charge transfer does not take place between Ar-S-TTF and fullerenes in the ground state. In this regard, the E 1/2 1 values of Ar-S-TTFs would not affect the formation of co-crystals.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…On the basis of hundreds of experimental runs, we found that the Ar-S-TTFs possessing the first redox potential ( E 1/2 1 ) smaller than 0.6 V could form the co-crystal-type complexes with fullerene molecules C 60 and/or C 70 , whereas those with E 1/2 1 > 0.6 V could not afford the desired complexes. The complexes obtained thus far are intrinsically neutral [ 63 ], which means the charge transfer does not take place between Ar-S-TTF and fullerenes in the ground state. In this regard, the E 1/2 1 values of Ar-S-TTFs would not affect the formation of co-crystals.…”
Section: Resultsmentioning
confidence: 99%
“… a CS 2 : carbon disulfide, PhCl: chlorobenzene; b the compositions of the co-crystals were determined by X-ray single crystal structure analysis; c see reference [ 63 ]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations